2021
DOI: 10.1186/s13002-021-00448-x
|View full text |Cite
|
Sign up to set email alerts
|

Homegarden agroecosystems managed by Salar people on Qinghai-Tibet Plateau

Abstract: Background Salar is a Turkic-speaking Islamic ethnic group in China living mainly in Xunhua Salar Autonomous County (Xunhua or Xunhua County), Qinghai-Tibet Plateau. Salar people are skilled in horticulture and their homegarden (HG) management. They are regarded as the first people on the Qinghai-Tibet Plateau to practice horticulture, especially manage their HGs, traditional farming systems, and supplementary food production systems. Traditional knowledge of Salar people associated with their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Sixty households (homegardens) were randomly selected in each village by lottery, and appropriate fine-tuning was conducted with the help of local guides. We collected the data using semi-structured face-to-face interviews with homegarden households [ 13 ]. Since some Baiku Yao in the study area could not speak fluent Mandarin, assistance was obtained from local guides during the fieldwork.…”
Section: Methodsmentioning
confidence: 99%
“…Sixty households (homegardens) were randomly selected in each village by lottery, and appropriate fine-tuning was conducted with the help of local guides. We collected the data using semi-structured face-to-face interviews with homegarden households [ 13 ]. Since some Baiku Yao in the study area could not speak fluent Mandarin, assistance was obtained from local guides during the fieldwork.…”
Section: Methodsmentioning
confidence: 99%
“…These homegardens provide a high diversity of cultivated plants for self-sufficiency and social values underpinning and contributing to cultural diversity [13][14][15]. Furthermore, homegardens are more sustainable and adapted to local demands because of the planting of traditional varieties and the use of traditional management practices [16][17][18]. Diversity in homegardens can be affected by the interactions among spatial, environmental, demographic, social, economic, and cultural factors to influence agricultural practices [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…China has a long history of traditional vegetable cultivation in homegardens, maintaining this vegetable cultivation [28,29]. Studies have shown homegardens can be a source of germplasm bank for the conservation of local varieties [30][31][32]. [35]In southwest China, homegardens are small-sized agroecosystems and provide an on-farm conservation strategy consistent with household socioeconomic characteristics [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%